PENDIDIKAN RAMAH ANAK DI SURAKARTA : SINERGITAS, KOMUNIKASI ORGANISASI, DAN MODAL SOSIAL - Mochammad Sinung Restendy (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
The child-friendly education program or Child-Friendly Schools (SRA) is a program initiated by UNICEF with the leading sector for each district city being the respective regional Women's and Child Protection Services. Program implementation cannot be carried out optimally without support and good communication from various parties as well as strong social capital in each region. Therefore, there is a need for synergy and cooperation between ministries, the private sector, local government and the community. With a research focus on the City of Surakarta, a Child Friendly City (KLA) with the Main title six times in a row since 2016, and is currently in the process of becoming a World Child Friendly City. The aim of this research is to determine the communication network built between institutions in realizing child-friendly education in Surakarta. What social capital is used to support organizational communication in realizing child-friendly education in Surakarta and knowing the impact of organizational communication in realizing child-friendly education in Surakarta for the institutions involved. This research methodology uses a qualitative phenomenological approach with data collection techniques through observation, in-depth interviews and document study. The research results show that UNICEF as the initiator encourages the leading sector to build a partnership network to create Child Friendly Schools (SRA) with more dominant organizational communication, formally based on the concept of dependency, openness, synergy and occurring in all directions. Policy, evaluation, program control, early learning of character, ethics or morals as social capital and supported by efforts to strengthen organizational resources. The impact of organizational communication carried out by DP3AP2KB Surakarta and service network partners is an integrated and integral system in handling cases including health, civil registration, education and certain cases in Child Friendly Schools.